A systematic mapping study of information visualization for software product line engineering. Issue 2 (8th November 2017) - Lopez‐Herrejon, Roberto Erick; Illescas, Sheny; Egyed, Alexander
Abstract: Software product lines (SPLs) are families of related systems whose members are distinguished by the set of features they provide. Over 2 decades of research and practice can attest to the substantial benefits of applying SPL practices such as better customization, improved software reuse, and faster time to market. Software product line engineering (SPLE) refers to the paradigm of developing SPLs. Typical SPLE efforts involve a large number of features that are combined to form also large numbers of products, implemented using multiple and different types of software artifacts. Because of the sheer amount of information and its complexity, visualization techniques have been used for different SPLE activities. In this paper, we present an extended systematic mapping study on this subject. Our research questions aim to gather information regarding the techniques that have been applied, at what SPLE activities, how they were implemented, the publication fora used, the methods of empirical evaluation, and the provenance of the evaluation examples. Our driving goal is to identify common trends, gaps, and opportunities for further research and application.